Presentation: Allpanchis in transition - Cabala Banda, Pamela (2021)
Hope, optimism and commitment were part of the values ​​deposited in the foundation of our Allpanchis magazine. Perhaps the best evidence of this is the name itself, which, in its Spanish version, intones the psalm: «our land will give its fruit», a profound interpellation that, in addition to the clear theological and pastoral agenda of its time, can be read as the commitment to the academic potential of our heritage. It did not take many years for the intellectual achievements of the research body of what was the Andean Pastoral Institute (IPA) to begin to be reaped, both companies run by a cohort of bishops, priests, nuns and pastoral agents. Within the research projects of the IPA, aimed at understanding the social processes and practices of its time from a religious and scientific perspective, Allpanchis played a key role in that it offered a space for reflection aimed at the actors of the local dioceses. Allpanchis had to reflect the new look of the IPA and, therefore, of the so-called "South Andean Church", to the Andean religious phenomenon. With Manuel Marzal in charge of the research area of ​​the recently founded IPA and editor of Allpanchis, studies in the anthropology of religion were promoted, while subsequent editors continued to produce now classic numbers for Peruvian social sciences.